Gastroretentive Drug Delivery Systems As A Potential Tool For Enhancing The Efficacy Of Antibiotics: A Review - N.H. FODA,; S.M. ALI, (International Journal of Pharma and Bio Sciences, 2011)
An optimum GRDF system can be defined as a system which retains in the stomach for a sufficient time interval against all the physiological barriers, releases active moiety in a controlled manner, and finally is easily metabolized in the body. This in turn improves bioavailability, reduces drug wastage, improves solubility of drugs that are less soluble at high pH environment. They also help in achieving local delivery of drug to the stomach and proximal small intestine, thus they were found to be suitable for formulating drugs with narrow therapeutic indices. Antibiotics belonging to different classes were proven to be good candidates for the formulation of GRDDS, therefore, the purpose of this paper is to review the recent literature and current technology used in the development of gastroretentive dosage form of various antibiotics.